A Review on Thin Layered Composite Zeolite for Water Desalination Applications - Norsuhailizah, Sazali; Zawati, Harun; Abdullahi, Tijjani; Norazlianie, Sazali; Mohamad Shaiful, Abdul Karim; Ahmad Syahiman, Mohd Shah (Akademi Baru, 2019)
Seawater one of the abundant water resources which is estimated covers about 71% of the earth’s surface which is existed either in the form of oceans and seas. Thus, gaining freshwater from seawater is one of the best alternatives by considering of serious problem of water contamination in our mainstream system. In the water treatment, reverse osmosis (RO) pre-treatment, chemical, and biotechnology industries, ultrafiltration membrane have been used extensively for separation processes. Desalination is one of the processes that eliminates mineral content found in saline water via water treatment process. Various approaches used in desalination include adsorption, ion exchange, distillation, evaporation, reverse osmosis and electrodialysis. Even with all of the existing techniques, researchers are still exploring new method that are safe, energy-efficient and simple to operate. Therefore, the use of adsorption technique is still applicable until now. Currently, scientists are focusing on providing new and effective ways of desalination, removing anions and cations by using superpower particle of zeolites. This review paper aims to compile studies done by researchers on the effect of various kaolin towards a hydrothermal synthesis of zeolite. Adsorption performance of zeolite towards desalination is also included together with its mathematical model for more understanding on its performance